2021
DOI: 10.3389/fpls.2021.743568
|View full text |Cite
|
Sign up to set email alerts
|

Differential Association of Free, Conjugated, and Bound Forms of Polyamines and Transcript Abundance of Their Biosynthetic and Catabolic Genes During Drought/Salinity Stress in Tomato (Solanum lycopersicum L.) Leaves

Abstract: Polyamines have been implicated in ameliorating the detrimental effects of drought and saline conditions on plant growth and development. The independent impact of these two abiotic stresses on polyamine (PA) biosynthesis, catabolism, and homeostasis, as well as on their transcript abundance in tomato leaves, is presented here. We show that the total levels of putrescine (PUT), spermidine (SPD), and spermine (SPM) increase up to 72 h during drought and up to 48 h during salinity stress before their precipitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 79 publications
0
4
1
Order By: Relevance
“…Analysis of polyamine levels in tomato plants under well‐watered and drought stress conditions showed that drought stress increases Put levels but does not affect those of Spd, Spm, and T‐Spm (Figure S10). These data seem to partially contradict previous data indicating variations of Spm and Spd levels under drought stress (Montesinos‐Pereira et al., 2014; Upadhyay et al., 2021; Wang et al., 2023). These differences may depend on the plant species and genotype analyzed, as well as on the duration, severity, and mode of drought stress (Montesinos‐Pereira et al., 2014; Wang et al., 2023).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Analysis of polyamine levels in tomato plants under well‐watered and drought stress conditions showed that drought stress increases Put levels but does not affect those of Spd, Spm, and T‐Spm (Figure S10). These data seem to partially contradict previous data indicating variations of Spm and Spd levels under drought stress (Montesinos‐Pereira et al., 2014; Upadhyay et al., 2021; Wang et al., 2023). These differences may depend on the plant species and genotype analyzed, as well as on the duration, severity, and mode of drought stress (Montesinos‐Pereira et al., 2014; Wang et al., 2023).…”
Section: Discussioncontrasting
confidence: 84%
“…Numerous reports support the contribution of the different polyamines in plant stress responses through a variety of mechanisms (Montesinos-Pereira et al, 2014;Wang & Liu, 2016;Liu et al, 2015;PĂĄl et al, 2018;AlcĂĄzar et al, 2020;Li et al, 2020;Hasan et al, 2021;Upadhyay et al, 2021;BlĂĄzquez, 2024). As considered T-Spm, exogenous application induced the expression of pathogenesis-related proteins and improved tolerance to biotic and abiotic stresses (AlcĂĄzar et al, 2020;Mo et al, 2015;Sagor et al, 2012;Shinohara et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Some previous studies have suggested that Put build-up could cause the injury induced by drought stress ( Pedrol et al, 2000 ) and other abiotic stresses ( Slocum, 1991 ; Rodriguez et al, 2001 ). Nevertheless, recent researches showed that the application of exogenous Put could enhance the tolerance of plants to drought stress ( Ebeed et al, 2017 ; Hassan et al, 2020 ; Upadhyay et al, 2021 ) and chilling stress ( Ahmad and Ali, 2019 ). Therefore, in the resistance of plants to environmental stresses, the precise significance of putrescine is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines regulate ethylene biosynthesis in relation to nitric oxide (NO) and hydrogen peroxide (H 2 O 2 ) during fruit abscission ( Parra-Lobato and Gomez-Jimenez, 2011 ; Gil-Amado and Gomez-Jimenez, 2012 ). The gene PAO4 is negatively correlated with salt stress and drought stress in tomato ( Upadhyay et al., 2021 ). The expression of ZmPAO2 , 3 , 4 , 5 , and 6 is increased in maize under drought stress ( Pakdel et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%